Pengaruh Kemudahan Penggunaan dan Manfaat yang Dirasakan terhadap Sikap dan Niat Pembelian Online (Studi pada Pembelian Batik di Jawa Timur) - R. Andi Sularso (Universitas Proklamasi 45 Yogyakarta, 2012)
The design of this study are included in the confirmatory research and research as well as explanatory. Analysis technique used is to use the Structural Equation Modeling (SEM).. Data retrieval techniques using purposive sampling method with the number of respondents 140 respondents. The results showed that: (1) Ease of use online shopping perceived significantly influence consumers 'attitude towards online purchases batik in East Java, (2) the perceived benefits of online shopping significantly influence consumers' attitude towards online purchases batik in East Java, (3) Ease of use online shopping perceived significant impact on repeat purchase intention online Batik in East Java, (4) the perceived benefits of online shopping does not significantly influence online purchase intentions in batik in East Java, (5) the attitude of influential consumers significant impact on repeat purchase intention online batik in East Java.